Fibrilação atrial e demência: resultados do São Paulo ageing & health study Atrial fibrillation and dementia: results from the Sao Paulo ageing & health study - Liz Andrea Kawabata-Yoshihara; Márcia Scazufca; Itamar de Souza Santos; Aristarcho Whitaker; Vitor Sérgio Kawabata; Isabela Martins Benseñor; Paulo Rossi Menezes; Paulo Andrade Lotufo (Arquivos Brasileiros de Cardiologia, 2012)
FUNDAMENTO: A fibrilação atrial é um fator de risco controverso para demência. OBJETIVO: O objetivo deste estudo é avaliar a associação entre fibrilação atrial e demência em participantes do São Paulo Ageing & Health. MÉTODOS: O São Paulo Ageing & Health é um estudo transversal, de base populacional, de idosos residentes em um uma região de baixa renda da cidade de São Paulo, Brasil. Diagnóstico de demência foi realizado de acordo com o protocolo do grupo 10/66, com base em critérios do Manual de Diagnóstico e Estatística das Perturbações Mentais (DSM-IV). O diagnóstico de fibrilação atrial foi feito por eletrocardiograma de 12 derivações, avaliado por dois cardiologistas. Dados demográficos e de fatores de risco cardiovasculares também foram obtidos. RESULTADOS: A demência foi diagnosticada em 66 (4,3%) e fibrilação atrial em 36 (2,4%) de 1.524 participantes com um eletrocardiograma válido. A razão de chances bruta para demência em participantes com fibrilação atrial foi 2,8 (intervalo de confiança [IC] 95%: 1,0-8,1; p = 0,06) em comparação com indivíduos sem fibrilação atrial. Relação positiva foi encontrada em mulheres (RC 4,2; IC 95%: 1,2-15,1; p = 0,03). Após ajuste para idade, no entanto, essa associação tornou-se não significativa (RC 2,2, IC 95%: 0,6-8,9; p = 0,26). CONCLUSÃO: Não houve associação independente entre a fibrilação atrial e demência nessa amostra. A prevalência da fibrilação atrial pode ser baixa nesta população em virtude da mortalidade cardiovascular prematura. BACKGROUND: Atrial fibrillation (AF) is a controversial risk factor for dementia. OBJECTIVE: The objective of this study was to assess the association between AF and dementia in the "Sao Paulo Ageing & Health" (SPAH) study participants. METHODS: SPAH is a cross-sectional, population-based study of elderly people living in a deprived neighborhood in Sao Paulo, Brazil. Dementia diagnosis was performed according to the 10/66 study group protocol based on Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) criteria. Diagnosis of AF was made using a 12-lead electrocardiogram (ECG) recording, which was assessed by two cardiologists. Data on demographics and cardiovascular risk factors were also obtained. RESULTS: Dementia was diagnosed in 66 (4.3%) and AF in 36 (2.4%) of 1,524 participants with a valid ECG. The crude odds ratio (OR) for dementia in participants with AF was 2.8 (95% confidence interval [CI]: 1.0-8.1; p=0.06) compared with individuals without AF. When analyzing data according to sex, a positive relationship was found in women (OR 4.2; 95% CI: 1.24-15.1; p=0.03). After age-adjustment, however, this association was no longer significant (OR 2.2; 95% CI: 0.6-8.9; p=0.26). CONCLUSION: There was no independent association between AF and dementia in this sample. The prevalence of AF may be low in this population owing to premature cardiovascular death.